Brand meaning management - MacInnis, Deborah J.; Park, C. Whan (Review of marketing research,, 2015)
Establishing, expanding and leveraging brand meaning is critically important yet exceedingly complex. Successful brand meaning management is foundational to both brand differentiation and to outcomes like brand identification and brand attachment. Yet, managing this meaning over time is complex. Noted contributors to this special issue add new insights to this complex domain. A group of papers lend insight into the myriad entities involved in the meaning making process itself, such as marketers, celebrities, brand users, and the broader culture in which consumers live. A second set emphasizes the critical impact that brand meaning has on consumers and brands themselvesâoutcomes that include brand identification and attachment, social relationship management, and brand evangelism. The final set addresses when and how brand transgressions can threaten these outcomes, and what brands must do to recover from lost or tainted meanings. The volume co-editors provide an overview of the chapters and identify future research issues on brand meaning management in B2B (vs. B2C) markets, and how multi-product firms manage the collective set of meanings that comprise their brand portfolio.